A potential signaling axis between RON kinase receptor and hypoxia‐inducible factor‐1 alpha in pancreatic cancer. Issue 11 (4th August 2021) - Kato, Akihisa; Ng, Serina; Thangasamy, Amalraj; Han, Haiyong; Zhou, Wendi; Raeppel, Stephane; Fallon, Michael; Guha, Sushovan; Ammanamanchi, Sudhakar
Abstract: The Cancer Genome Atlas (TCGA) of a pancreatic cancer cohort identified high MST1R (RON tyrosine kinase receptor) expression correlated with poor prognosis in human pancreatic cancer. RON expression is null/minimal in normal pancreas but elevates from pan‐in lesions through invasive carcinomas. We report using multiple approaches RON directly regulates HIF‐1 α, a critical driver of genes involved in cancer cell invasion and metastasis. RON and HIF‐1 α are highly co‐expressed in the 101 human PDAC tumors analyzed and RON expression correlated with HIF‐1 α expression in a subset of PDAC cell lines. knockdown of RON expression in RON positive cells blocked HIF‐1 α expression, whereas ectopic RON expression in RON null cells induced HIF‐1 α expression suggesting the direct regulation of HIF‐1 α by RON kinase receptor. RON regulates HIF‐1 α through an unreported transcriptional mechanism involving PI3 kinase‐mediated AKT phosphorylation and Sp1‐dependent HIF‐1 α promoter activity leading to increased HIF‐1 α mRNA expression. RON/HIF‐1 α modulation altered the invasive behavior of PDAC cells. A small‐molecule RON kinase inhibitor decreased RON ligand, MSP‐induced HIF‐1 α expression, and invasion of PDAC cells. Immunohistochemical analysis on RON knockdown orthotopic PDAC tumor xenograft confirmed that RON inhibition significantly blocked HIF‐1 α expression. RON/HIF‐1 α co‐expression also exists in triple‐negative breast cancer cells, a tumor type that also lacks molecular therapeutic targets. This is the first report describing RON/HIF‐1 α axis in any tumor type and is a potential novel therapeutic target.